1994
DOI: 10.2166/wst.1994.0495
|View full text |Cite
|
Sign up to set email alerts
|

Optimization for Reduction/Precipitation Treatment of Hexavalent Chromium

Abstract: This paper describes wastewater treatment optimization studies performed on an industrial wastewater generated in Boston, Massachusetts, USA. The manufacturing plant generates hexavalent chromium [Cr(VI)] wastewater as a result of chromating brass, bronze and copper parts produced in the manufacturing operations. The facility utilizes a continuous flow treatment train, involving segregated Cr(VI) reduction with sodium metabisulfite (Na2S2O5) under acidic conditions, followed by combined wastestream two-stage p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Other iron solids present in water distribution pipes, such as hematite, magnetite, ilmenite, and green rusts can also serve as a source of ferrous iron for Cr(VI) reduction (Loyaux-Lawniczak et al, 2000;Kiyak et al, 1999;Khaodhiar, 1997;Peterson et al, 1997a;Peterson et al, 1997b;Peterson, 1996;White & Peterson, 1996;Eary & Rai, 1989;Anderson et al, 1984). Cr(VI) can also be reduced by many reduced sulfur compounds, including thiols (Szulczewski et al, 2001), iron sulfide (Kim et al, 2001;Patterson et al, 1997;Zouboulis et al, 1995), metabisulfite (Patterson et al, 1994), sodium sulfide and sodium sulfite (Lai & McNeill, 2006;Brandhuber et al, 2004), and hydrogen sulfide (Kim et al, 2001;Pettine et al, 1998a) as well as stannous chloride (Lai & McNeill, 2006;Brandhuber et al, 2004), ascorbic acid (Xu et al, 2004), and a variety of organic compounds (Buerge & Hug, 1998;Hug et al, 1997;Deng & Stone, 1996;Wittbrodt & Palmer, 1996;Wittbrodt & Palmer, 1995;Popov et al, 1992;James & Bartlett, 1983;Bartlett & Kimble, 1976;Schroeder & Lee, 1975). Cr(VI) can also be reduced under aerobic and anaerobic conditions by microbes; this can involve direct reduction by Cr-reducing bacteria as well as indirect reduction via production of hydrogen sulfide or ferrous iron by sulfate-reducing and iron-reducing bacteria, respec-tively (Boni & Sbaffoni, 2009;Somasundaram et al, 2009;Vainshtein et al, 2003;…”
Section: Figurementioning
confidence: 99%
“…Other iron solids present in water distribution pipes, such as hematite, magnetite, ilmenite, and green rusts can also serve as a source of ferrous iron for Cr(VI) reduction (Loyaux-Lawniczak et al, 2000;Kiyak et al, 1999;Khaodhiar, 1997;Peterson et al, 1997a;Peterson et al, 1997b;Peterson, 1996;White & Peterson, 1996;Eary & Rai, 1989;Anderson et al, 1984). Cr(VI) can also be reduced by many reduced sulfur compounds, including thiols (Szulczewski et al, 2001), iron sulfide (Kim et al, 2001;Patterson et al, 1997;Zouboulis et al, 1995), metabisulfite (Patterson et al, 1994), sodium sulfide and sodium sulfite (Lai & McNeill, 2006;Brandhuber et al, 2004), and hydrogen sulfide (Kim et al, 2001;Pettine et al, 1998a) as well as stannous chloride (Lai & McNeill, 2006;Brandhuber et al, 2004), ascorbic acid (Xu et al, 2004), and a variety of organic compounds (Buerge & Hug, 1998;Hug et al, 1997;Deng & Stone, 1996;Wittbrodt & Palmer, 1996;Wittbrodt & Palmer, 1995;Popov et al, 1992;James & Bartlett, 1983;Bartlett & Kimble, 1976;Schroeder & Lee, 1975). Cr(VI) can also be reduced under aerobic and anaerobic conditions by microbes; this can involve direct reduction by Cr-reducing bacteria as well as indirect reduction via production of hydrogen sulfide or ferrous iron by sulfate-reducing and iron-reducing bacteria, respec-tively (Boni & Sbaffoni, 2009;Somasundaram et al, 2009;Vainshtein et al, 2003;…”
Section: Figurementioning
confidence: 99%
“…Here, it will be pertinent to make a cost comparison between the conventional methods (ferrous sulfate or sodium sulfite) and that based on ZVI of chromium(VI) reduction. Patterson et al (1994) and Wichern (2004) reported almost complete removal of chromium(VI) by ferrous sulfate in an acidic medium using approximately 8 times the stoichiometric quantity of the reagent. McGuire et al (2006), who used sodium sulfite as the reducing agent, reported 100% excess requirement of the reagent.…”
Section: Introductionmentioning
confidence: 99%
“…Several procedures6–17 have been proposed for the treatment of chromium‐containing wastewater in order to reduce its concentration and to meet increasingly strict consent levels and regulations 6. Current methods for the treatment of Cr(VI) in liquid effluent include chemical precipitation, where reducing agents such as SO 2 , NaHSO 4 and FeSO 4 are used,8–11 and electrochemical precipitation, in which Fe 2+ ions are formed by electrochemical oxidation of iron anodes 12, 13. In both these techniques, the chromium ions are precipitated in settling ponds as hydroxide by pH adjustment.…”
Section: Introductionmentioning
confidence: 99%